Clues to membrane fouling hidden within the microbial communities of membrane bioreactors. Issue 8 (12th June 2019) - Weerasekara, Nuwan Asanka; Woo, Sung-Geun; Criddle, Craig; Iqbal, Tahir; Lee, Kibaek; Park, Yeong-Jun; Shin, Jae-Ho; Choo, Kwang-Ho
Abstract : Membrane bioreactors (MBRs), operated under the same conditions, encountered different fouling patterns. The MBR with severer membrane fouling had a relatively high abundance of specific bacteria groups. Abstract : Membrane fouling is the major bottleneck limiting widespread adoption of membrane bioreactors (MBRs), but its root causes are not yet fully understood. In this study, different fouling patterns were observed for replicate MBRs seeded with the same inoculum and maintained under identical operating conditions, with similar levels of biomass, soluble microbial products, and extracellular polymeric substances. None of these had significant correlations with membrane fouling. Exogenous colloidal particles from a real plant did not have an impact on fouling propensity. Fouling appeared to be correlated with increased abundance of specific classes of bacteria, notably Alphaproteobacteria, Sphingobacteria, and Flavobacteria . The membrane biofouling layer had a different community structure from MBR mixed liquor, showing the two dominant phyla Proteobacteria and Chloroflexi .